Integrated focal psychotherapy: Results from a retrospective study - Gislon, Maria Clotilde; Sattin, Davide; Cis, Mattia; Fiaschi, Mara; Tognasso, Giacomo; D’Ambrosio, Vincenzo; Villa, Maria; Ruffino, Milena; Bergamaschi, Susanna (Frontiers in Psychology, 2023)
Background The focus-based integrated model (FBIM) is a form of psychotherapy that integrates psychodynamic and cognitive psychotherapy and Erikson’s life cycle model. Although there are many studies on the effectiveness of integrated models of psychotherapy, few have examined the efficacy of FBIM. Objective This pilot study explores clinical outcome measures concerning individual wellbeing, the presence/absence of symptoms, life functioning, and risk in a cohort of subjects after they received FBIM therapy. Methods A total of 71 participants were enrolled at the CRF Zapparoli Center in Milan, 66.2% of whom were women (N = 47). The mean age of the total sample was 35.2 years (SD = 12.8). We used the Clinical Outcomes in Routine Evaluation–Outcome Measure (CORE-OM) to test treatment efficacy. Results The results revealed that participants improved in all four dimensions of CORE-OM (i.e., wellbeing, symptoms, life functioning, and risk), women improved more than men, and in most cases (64%), the change was clinically reliable. Conclusion The FBIM model seems to be effective for treating several patients. Most of the participants saw significant changes in symptoms, life functioning, and general wellbeing.